Impact of climate change on the long-term water balance in the Yarlung Zangbo basin - Deng, Yukun; Yao, Yingying; Zhao, Yufeng; Luo, Dongliang; Cao, Bin; Kuang, Xingxing; Zheng, Chunmiao (Frontiers in Earth Science, 2023)
The Himalayan and Tibetan Plateau (TP) region serves as the “Asian water tower”. Yarlung Zangbo basin (YZB) is one of most important major rivers originating from TP sustaining billions of lives in the downstream alluvial plain. Climate change has impacted the hydrological cycle in this alpine region; however, the temporal and spatial trends of runoff and the water balance has not been quantified adequately. Here, we have optimized the snowmelt module of the Soil and Water Assessment Tool (SWAT) for the YZB to quantify the historical and future variability in the runoff, snowmelt water, and water balance components. According to the results of CMIP5 and CMIP6, the future precipitation (2020-2099) projected by the Coupled Model Intercomparison Project Six (CMIP6) will increase by 2.7% when compared to historical reference (1980-2019), while the precipitation will increase by 10.2% when projected by CMIP5. The increase in average air temperature (2.4 °C) projected by CMIP6 exceeds that of CMIP5 (1.9 °C). The runoff between 2020 and 2050 will decrease by -12.7% compared with historical reference, and it will further decline by -9.2% during 2060 and 2099. Based on the average results of CMIP5 and CMIP6, the water balance deficit will increase primarily due to an increase in evaporation of 42.4%, whereas snowmelt (-32.1%), water yield (-9.4%), soil water (-19.8%), and groundwater recharge (-17.8%) will decrease. Long-term water balance evaluation implicates that middle and upper reaches will face a higher risk of drought, implying a potential threat to the sustainability of grassland ecosystems upstream.